2021
DOI: 10.1007/s11540-021-09524-x
|View full text |Cite
|
Sign up to set email alerts
|

Crop Cycle Length Determines Optimal Transplanting Date for Seedlings from Hybrid True Potato Seeds

Abstract: The technology of hybrid breeding in diploid potatoes creates opportunities to design novel and improved cultivation systems based on hybrid true potato seeds. A promising cultivation pathway to produce seed or ware tubers is by transplanting greenhouse-raised seedlings into the field. This study explored the effects of transplanting date and seedling age on tuber yield, using greenhouse-raised seedlings. Field trials with experimental hybrid genotypes were conducted in three consecutive years. In 2017 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…En cuanto a los criterios climáticos de temperatura (26 %) y precipitación (16 %), la temperatura tiene mayor importancia en este estudio; esto se debe a que está asociada a la presencia de enfermedades (Bourke, 1993) y riesgos climáticos como heladas (van Dijk et al, 2022). El cultivo de papa requiere entre 400-1200 mm durante todo el año (Mandal et al, 2020) y es de gran importancia en los diferentes periodos de crecimiento (Jiang & Yang, 2022).…”
Section: Discussionunclassified
“…En cuanto a los criterios climáticos de temperatura (26 %) y precipitación (16 %), la temperatura tiene mayor importancia en este estudio; esto se debe a que está asociada a la presencia de enfermedades (Bourke, 1993) y riesgos climáticos como heladas (van Dijk et al, 2022). El cultivo de papa requiere entre 400-1200 mm durante todo el año (Mandal et al, 2020) y es de gran importancia en los diferentes periodos de crecimiento (Jiang & Yang, 2022).…”
Section: Discussionunclassified
“…In recent years, the use of field transplanted, nursery-raised, hybrid potato seedlings has been tested as a potential alternative system for seed and ware potato production [ 54 ]. Ultimately, to obtain a highly productive transplanted crop, aspects of seedling production, field establishment and transplant field crop management need be considered and successfully executed [ 55 ].…”
Section: Cropping Systemsmentioning
confidence: 99%
“…Transplanting densities of 25 and 50 plants m −2 resulted in optimum tubers yields in contrasting planting systems. We observed that tuber-size distribution was affected having an increasing share of large-sized tubers when planting density decreases [ 54 ]. Timing of transplants in spring and stage of the transplant are important new agronomic decisions that need to be taken.…”
Section: Cropping Systemsmentioning
confidence: 99%
See 2 more Smart Citations